Hard-core collisional dynamics in Hamiltonian mean-field model - Melo, I.; Figueiredo, A.; Rocha Filho, T.M.; Miranda Filho, L.H.; Elskens, Y. (Communications in nonlinear science & numerical simulation, 2020)
•Systems with long range interactions have drawn a great deal of attention over the last few decades, not only because they are common in nature (e.g. self-gravitating systems and charged plasmas), but also due to many unusual phenomena not observed in short-range interacting systems. In the present paper we discuss for the Hamiltonian mean-field model, a much studied system, the effects on the system dynamics of the introduction of a hard-core point-like interaction, resulting in a system with both global and strong short-range interactions.•We developed a numeric algorithm for the molecular dynamics of this type of mixed interaction, and applied it to understand how the violent relaxation and the long-term dynamics are altered.•This is a first and original step to understand how the special phenomenology of long-range interacting systems is altered by hard-core potentials, and point to new research and relevant open problems. We consider a modification of the well studied Hamiltonian Mean-Field model with cosine potential by introducing a hard-core point-like repulsive interaction and propose a numerical integration scheme to integrate its dynamics. Our results show that the outcome of the initial violent relaxation is altered, and also that the phase-diagram is modified with a critical temperature at a higher value than in its counterpart without hard-core collisions.